Prospective study on the outcomes of harmonic scalpel assisted thyroidectomy in a tertiary care centre in South Kerala - Sasindran, Vivek; John, Mithra S.; B., Arunkrishna; B., Harikrishan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: To estimate the outcomes of thyroidectomy using harmonic scalpel in terms of intra-operative and post-operative blood loss, operating time, incidence of post-operative hypocalcaemia, incidence of recurrent laryngeal nerve and superior laryngeal nerve palsy and post-operative pain. Methods: The patients are selected consecutively as and when they were presented during the study period. The study involved 23 patients out of which 17 underwent total thyroidectomy and 6 underwent hemithyroidectomy, all using harmonic scalpel. A complete history, physical examination and appropriate investigations were done to arrive at the correct diagnosis. Surgery was done and all the parameters were accurately assessed. Results: The mean intra-operative and post-operative blood loss in thyroidectomy by harmonic scalpel was 92.2 ml and 20.6 ml respectively. The mean operative time for thyroidectomy using harmonic scalpel was 58.2 minutes that includes 38 minutes for hemi thyroidectomy and 65.3 minutes for total thyroidectomy. Out of 23 patients, only 1 patient (4.3%) had transient hypocalcaemia in the post operative period. Three patients (13%) had transient unilateral recurrent laryngeal nerve palsy and none had superior laryngeal nerve palsy. The pain assessment by visual analog scale (VAS) score at 24 hours and 48 hours after harmonic scalpel assisted thyroidectomy were 3.87±0.97 and 2.35±1.30 respectively. Conclusions: Harmonic scalpel gives effective and reliable hemostasis, shortens the operative time, reduces the complications and improved pain control and hence may be considered as an effective tool in thyroidectomy.